A mobile middleware to solve interoperability problems in VOIP streaming session. (1st January 2012) - Kamal, Rossi; Kamal, Mosaddek Hossain; Monowar, Muhammad Mostafa; Hong, Choong Seon
SIP, H.323 and Jingle have been widely used as VoIP protocols. As the session establishment period differs in these protocols and their different implementations, interoperability problems occur. This paper presents a middleware on mobile devices with a generic framework supporting the three protocols and their different implementations. The applications (rmobvoip, rmoblog, mobrmi, mobcorba) implement distributed protocols to solve interoperability problems and to overcome the scarce resources of mobile devices. A peer with this middleware is provided with three options (SIP, H.323 and Jingle) and it can choose any of the protocols or implementations depending on the protocol type used by other peer of the session.